A Histopathological-Biochemical Health Assessment of Blue Mussel Mytilus edulis - Jones, Connor P.; St. Gelais, Adam T.; Byron, Carrie J.; Costa-Pierce, Barry A.; Smolowitz, Roxanna M.; Condon, Michele E.; Parker, Katherine E.; Jane, Aubrey E.; Shippey, Elena G. (Journal of Shellfish Research, 2021)
Aquaculture of the blue mussel Mytilus edulis in the Gulf of Maine is a growing industry at a time when wild mussel populations are threatened by a rapidly changing ocean. Intertidal mussel beds have largely disappeared in the region raising concerns over the long-term viability of mussel farming. Histology and lipid fatty acid analysis were used to assess gametogenesis, energy investment, and pathology of farmed mussels collected twice monthly for three years in Casco Bay, ME. Energy investment in reproduction and storage differed significantly between years, suggesting interannual variability. Wet weight of fatty acids such as DHA and EPA corresponded to pre-spawning periods, when gonad tissue was most abundant. Overall, pathology assessment showed low levels of common pathogens, parasites, and cellular abnormalities. The survey did, however, reveal high levels of oocyte atresia, a probable indicator of physiological or environmental stress from unfavorable spawning conditions. In addition, the presence of the potentially damaging digenetic trematode Proctoeces maculatus was documented using histology, marking the northernmost detection in the Northwest Atlantic and a likely climate-driven range expansion. These trends may signal a challenging future for blue mussels in the Gulf of Maine. Forward-looking farm mitigation practices informed by these results should be developed to ensure future sustainability of this industry.